Evaluation of exercise-induced modulation of glial activation and dopaminergic damage in a rat model of Parkinson's disease using [11C]PBR28 and [18F]FDOPA PET. Issue 6 (June 2019) - Real, Caroline C; Doorduin, Janine; Kopschina Feltes, Paula; Vállez García, David; de Paula Faria, Daniele; Britto, Luiz R; de Vries, Erik FJ
Evidence suggests that exercise can modulate neuroinflammation and neuronal damage. We evaluated if such effects of exercise can be detected with positron emission tomography (PET) in a rat model of Parkinson's disease (PD). Rats were unilaterally injected in the striatum with 6-hydroxydopamine (PD rats) or saline (controls) and either remained sedentary (SED) or were forced to exercise three times per week for 40 min (EX). Motor and cognitive functions were evaluated by the open field, novel object recognition, and cylinder tests. At baseline, day 10 and 30, glial activation and dopamine synthesis were assessed by [ 11 C]PBR28 and [ 18 F]FDOPA PET, respectively. PET data were confirmed by immunohistochemical analysis of microglial (Iba-1) / astrocyte (GFAP) activation and tyrosine hydroxylase (TH). [ 11 C]PBR28 PET showed increased glial activation in striatum and hippocampus of PD rats at day 10, which had resolved at day 30. Exercise completely suppressed glial activation. Imaging results correlated well with post-mortem Iba-1 staining, but not with GFAP staining. [ 18 F]FDOPA PET, TH staining and behavioral tests indicate that 6-OHDA caused damage to dopaminergic neurons, which was partially prevented by exercise. These results show that exercise can modulate toxin-induced glial activation and neuronal damage, which can be monitored noninvasively by PET.